“Followership” - The Missing Puzzle in Educational Leadership Research - Lee, Jun Choi; Yeo, Siew Pey; Abdul Halim, Busari; Zaiton, Hassan (Human Resource Management Academic Research Society (www.hrmars.com), 2021)
Over the past three decades, many scholars have begun to view followers as assets in understanding leadership. However, limited studies have explored the potential impact of followership on educational leadership, particularly in school settings. Therefore, the goal of this paper is to review the teachers’ followership styles in literature from 1997 to 2018 in school settings with reference to the Kelley Followership Model. The findings have shown that most of the teachers are categorised as exemplary followers. This group of teachers acquired high scores in independent critical thinking skills and are actively engaged in school activities. Exemplary teachers may equip schools to improve and sustain their performance. Good followership can be strengthened by dyadic relationships between leaders and followers. This relationship is imperative as it shapes the development of pragmatic strategies that help to promote leadership effectiveness. The results benefit both school leaders and teachers in recognizing the value to cultivate a dignified leader-follower relationship.